Optimasi Layanan KKN: Implementasi e-KKN Berbasis Web Pada Universitas Islam Lamongan - Danang Bagus Reknadi; M Munif; M Mustain (LPPM STIKOM Tunas Bangsa, 2024)
The college is an educational institution that aims to create scientist environmentally sensitive and able to solve the problems that arise in society and have a responsibility to produce graduates who are professionals so that they can support and handle the problems that arise in the community. In order to realize the objective and responsibility, each college must carry out activities Kuliah Kerja Nyata (KKN). KKN is a form of community service, which is special, because there is an element in the Tri Dharma of Universities, namely: Education and Teaching, Research, Service society. The rapid development of science and technology and the progress of communication tools. The need for a renewal of KKN administrative system, called e-KK. These features are provided runs in accordance with has been drafted, with the SIAKAD data as a reference database. The purpose of the development of e-KKN is to accommodate the needs of the KKN administrative process neat for processing data quickly, accurately, and effectively at the Islamic University of Lamongan. In the design, e-KKN has several features that have been prepared in accordance groove mechanism of opening the registration portal, process list, the small groups at random, until data printing user.